Probing Physical Properties of a DNA‐Protein Complex Using Nanofluidic Channels. Issue 5 (2nd January 2014) - Frykholm, Karolin; Alizadehheidari, Mohammadreza; Fritzsche, Joachim; Wigenius, Jens; Modesti, Mauro; Persson, Fredrik; Westerlund, Fredrik
<x xml:space="preserve">Abstract</x> A method to investigate physical properties of a DNA‐protein complex in solution is demonstrated. By using tapered nanochannels and lipid passivation the persistence length of a RecA filament formed on double‐stranded DNA is determined to 1.15 μm, in agreement with the literature, without attaching protein or DNA to any handles or surfaces. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>